Effects of nuclear deformation on the form factor for direct dark matter detection - 陈亚正 谌俊谋 罗延安 申虹 李学潜 (Chinese physics C, 2012)
For the detection of direct dark matter, in order to extract useful information about the funda- mental interactions from the data, it is crucial to properly determine the nuclear form factor. The form factor for the spin-independent cross section of collisions between dark matter particles and the nucleus has been thoroughly studied by many authors. When the analysis was carried out, the nuclei were always supposed to be spherically symmetric. In this work, we investigate the effects of the deformation of nuclei from a spherical shape to an ellipticM one on the form factor. Our results indicate that as long as the ellipticity is not too large, such deformation will not cause any substantial effects. In particular, when the nuclei are randomly orientated in room-temperature circumstances, one can completely neglect them.